Effect of dorsiflexion shoes on the energy cost of running - Buchheit, M.; Laursen, P. B.; Leblond, F.; Ahmaidi, S. (Science & Sports, 2010)
To evaluate the effect of dorsiflexion shoes on the energy cost of running (Cr), with or without noticeable acute neuromuscular fatigue.